Behind the scenes: How RNA orchestrates the epigenetic regulation of gene expression - Mangiavacchi, Arianna; Morelli, Gabriele; Orlando, Valerio (Frontiers in Cell and Developmental Biology, 2023)
Non-coding DNA accounts for approximately 98.5% of the human genome. Once labeled as “junk DNA”, this portion of the genome has undergone a progressive re-evaluation and it is now clear that some of its transcriptional products, belonging to the non-coding RNAs (ncRNAs), are key players in cell regulatory networks. A growing body of evidence demonstrates the crucial impact of regulatory ncRNAs on mammalian gene expression. Here, we focus on the defined relationship be-tween chromatin-interacting RNAs, particularly long non-coding RNA (lncRNA), enhancer RNA (eRNA), non-coding natural antisense transcript (ncNAT), and circular RNA (circRNA) and epigenome, a common ground where both protein and RNA species converge to regulate cellular functions. Through several examples, this review provides an overview of the variety of targets, interactors, and mechanisms involved in the RNA-mediated modulation of loci-specific epigenetic states, a fundamental evolutive strategy to orchestrate mammalian gene expression in a timely and reversible manner. We will discuss how RNA-mediated epigenetic regulation impacts development and tissue homeostasis and how its alteration contributes to the onset and progression of many different hu-man diseases, particularly cancer.